Vegetative Propagation of Adina cordifolia (Roxb.) Hook. F. Ex Brandis - Kaushal, Rajesh; Jeena, L. S.; Chaturvedi, S.; Tewari, L.; Tewari, S. K. (Indian Forester, 2010)
The paper reports for the first time rooting in Adina cordifolia using macropropagation technique. Two different types of cuttings viz. branch cuttings (hardwood, semihardwood and softwood) and mono nodal leafy softwood cuttings, prepared from epicormic shoots were treated with 4000 and 6000 ppm IBA for 10 seconds. The results revealed that hardwood and semi-hardwood cuttings failed to root even with the application of IBA. Softwood cuttings prepared from terminal portion of the lateral branches showed 15 to 18 per cent rooting with the application of IBA. Mono nodal leafy softwood cuttings resulted in 62.5 per cent rooting with the application of 4000 ppm IBA. The rooting increased to 75 per cent when the concentration was increased to 6000 ppm IBA. Other rooting and sprouting parameters also showed similar pattern.